2014
DOI: 10.1080/13691058.2014.911960
|View full text |Cite
|
Sign up to set email alerts
|

The other side of the bridge: exploring the sexual relationships of men who have sex with men and their female partners in Mumbai, India

Abstract: Behaviourally bisexual men have been identified as a ‘bridge’ population of HIV transmission to heterosexual women in India. Little is known about the sexual relationships that these men have with their female sex partners. The primary objective of this study was to explore the sexual practices and relationship dynamics between married and unmarried behaviourally bisexual men and their female sex partners in Mumbai, India. In 2009, semi-structured qualitative interviews were conducted with 32 men who reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Recent studies targeting migrant men (Saggurti, Mahapatra, Sabarwal, Ghosh, & Johri, 2012; Saggurti, Nair, et al, 2012) have documented bisexual behavior among migrant population in India. Additionally, over 60% of our participants were not currently married, yet identify themselves as “bisexual.” This is a major difference between our sample and participants from other studies (Closson et al, 2014; Kumta et al, 2010a) in which they conceptualize bisexual men solely in terms of being “married MSM”. The few ongoing sexual health research and practice initiatives in India that have focused on “behaviorally bisexual” men have targeted MSM who are partnered in the context of marriage with a female partner.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Recent studies targeting migrant men (Saggurti, Mahapatra, Sabarwal, Ghosh, & Johri, 2012; Saggurti, Nair, et al, 2012) have documented bisexual behavior among migrant population in India. Additionally, over 60% of our participants were not currently married, yet identify themselves as “bisexual.” This is a major difference between our sample and participants from other studies (Closson et al, 2014; Kumta et al, 2010a) in which they conceptualize bisexual men solely in terms of being “married MSM”. The few ongoing sexual health research and practice initiatives in India that have focused on “behaviorally bisexual” men have targeted MSM who are partnered in the context of marriage with a female partner.…”
Section: Discussionmentioning
confidence: 84%
“…This provides further evidence that these are not simply men who are “actually gay” but who engage in sexual behavior and relationships with female partners to conform to society’s standards, as some incorrectly assume about bisexual individuals in cultural context such as India, particularly “married MSM” (Closson et al, 2014). These are men who, in addition to self-identifying as “bisexual,” are seeking out, engaging in, and enjoying sexual behaviors with both men and women, providing further rationale for focusing on “bisexually-oriented” men as separate and distinct from other sub-populations of behaviorally bisexual men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homosexuality is criminalized in Section 377 of the Penal Code and stigmatization of homosexuality and discrimination remain pervasive, limiting access to HIV-related services and contributing to poor psychosocial health [48]. Qualitative research has found numerous negative life experiences among MSM, including childhood sexual abuse, lack of family- and community- acceptance, pressure to marry, harassment and violence [6, 813]. Both qualitative and quantitative studies have identified significant psychosocial concerns among MSM in India, including high levels of psychological distress, depression, anxiety, suicidal ideation, and substance use [4, 5, 7, 8, 1422].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual behavior in India may vary without regard to sexual identity or dominant orientation (Closson et al, 2014; Dey et al, 2011). Indian MSM have developed a distinct lexicon through which they refer to themselves and other male sexual partners, including terms such as kothi (receptive and effeminate partner), panthi (insertive and masculine partner), and double decker (both insertive and receptive partner) (Aggarwal, Sharma, & Chhabra, 2000; Asthana & Oostvogels, 2001;Boyce, 2007; Chakrapani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%